Linguacultural Peculiarities Of Somatic Phraseological Units In The English And Uzbek Languages - Pulatova Shokhsanam Sobirjonovna (Zien Journals, 2025)
This article examines the linguacultural features of somatic phraseological units (SPUs) in English and Uzbek. SPUs—idiomatic expressions involving body parts—reveal rich insights into cultural worldviews and shared human experiences. The study explores their formation, meanings, and functions, highlighting both universal and culture-specific elements. A contrastive analysis illustrates how SPUs encode values, emotions, and perceptions through somatic imagery in each language. The findings contribute to phraseological theory, intercultural communication, and language pedagogy
Keywords: somatic phraseological units; body idioms; linguaculture